The road toward imaging a black hole: A personal perspective - Falcke, Heino (Natural sciences (Weinheim), 2022)
The images of the supermassive black holes Sgr A* and M87* by the Event Horizon Telescope collaboration mark a special milestone in the history of the subject. For the first time, we are able to see the shadow of black holes, testing basic predictions of the theory of general relativity. We are also now learning more about the fundamental astrophysical processes close to the event horizon that help to shape entire galaxies and even parts of our cosmos. The ultimate result was only possible due to a large collaborative effort of scientists and institutions around the world. The road toward these images was the result of a long sociological and scientific process. It started with early pathfinder experiments and a few simple ideas that were remarkably successful in predicting the basic observational signatures to look for. This was based on the premise that black holes are inherently simple objects. Here, I describe this journey and some lessons learned from a personal perspective. The article describes the authors personal journey towards developig the Event Horizon Telescope and the first image of a black hole. Left: predcition made by the author and collaborators proposing the black hole imaging in 2000. Right: the two images observed and published by the Event Horizon Telescope in 2019 and 2022.